The contribution of IFPRI research and the impact of the Food for Education Program in Bangladesh on schooling outcomes and earnings - Ryan, James G.; Meng, Xin (International Food Policy Research Institute, 2004)
This paper evaluates the influence and impact that IFPRI research and related activities had on the initiation, evolution, and impact of the food for education (FFE) program in Bangladesh. It reviews the outputs from the IFPRI program and summarizes the perceptions of various stakeholders about the value and influence of these on the FFE program. A novel experimental evaluation methodology is used on household sample survey data to analyze the effects of FFE on schooling outcomes. Earnings functions are then estimated using national household income and expenditure survey data to assess the effect of schooling on earnings. Combining the two, the effects of the increased participation and duration of schooling (due to the FFE program) on lifetime earnings of children are derived. Using these incremental earnings figures, the internal rates of return for both national and private investments in the FFE program are estimated. From these, a conservative assessment of the economic value of IFPRI's contribution to the generation of the national benefits is made... We conclude that a very conservative assessment of the economic value of IFPRI's contribution to the generation of the national benefits estimated above is that the FFE program began one year earlier than it might have without the IFPRI input. Based upon the total cost of the IFPRI-FFE research program of US$151,000, the internal rate of return on this research investment ranges from 64-96 percent. of all the other benefits are added to this, clearly the IFPRI contribution has been an outstanding economic investment. These benefits might have been even greater had IFPRI had an explicit communications strategy with more timely and available publications, along with appropriate advocacy based upon a more thorough knowledge of the dynamic political economy of government decision making in Bangladesh." -- from Authors' Abstract